Mapping the structural evolution in the global scrap copper trade network. (1st December 2020) - Wang, Chao; Huang, Xia; Lim, Ming K.; Tseng, Ming-Lang; Ghadimi, Pezhman
Abstract: The rise in industrialization and urbanization has elevated consumer lifestyles and has dramatically increased copper consumption in the past three decades. Due to the growing scarcity of copper ore and lower manufacturing costs associated with using recycled copper, copper recycling has gained increasing attention. Because of the uneven geographical distribution of scrap copper, the international scrap copper trade has formed and is experiencing rapid growth. This study applies complex network theory to map the structural evolution of the global scrap copper trade from 1988 to 2017 according to the UN-Comtrade database. The results show that the global scrap copper trade has been reshaped from the pre-existing geopolitical realities through the interaction of geopolitical relations and geo-economics. The America-Asia community is the largest trading community and is driven by the USA and China. China is the largest recipient of scrap copper due to a lack of self-sufficiency with respect to copper and scrap copper resources. India is considered another long-term potential market for exporters, which can result in reducing dependence on a single market such as China. These findings, together with policy-related discussions, help authorities understand the complex international scrap copper trade relationships and propose effective import-export policies to reduce the risk of trade disruption. Highlights: A global scrap copper trade network is analyzed using complex network theory. The network is reshaped by the interaction of geopolitical relations and geo-economics. The American-Asian community is the largest trading community. China is the largest recipient of scrap copper. India is considered as another long-term potential market for exports.